1989
DOI: 10.2337/diab.38.11.1417
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Glucose on Insulin Secretion by Isolated Rat Islets and Purified β-Cells and Possible Role of Glycosylation

Abstract: We investigated the effect of 24 h of exposure to various glucose concentrations on insulin secretion by isolated rat pancreatic islets and purified rat beta-cells. Compared with islets cultured with standard medium (5.5 mM glucose), islets cultured with 16.7 mM glucose showed a higher basal insulin release (means +/- SE, 3.0 +/- 0.5 vs. 0.7 +/- 0.2%, n = 8, P less than .005) and reduced glucose-stimulated insulin secretion (2.4 +/- 0.3 vs. 5.8 +/- 0.4%, n = 8, P less than .005). Similar results were also obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
1
1

Year Published

1991
1991
2002
2002

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 0 publications
2
28
1
1
Order By: Relevance
“…However, whether metformin also affects glucose and FFA oxidation in other tissues, including the pancreatic ␤-cells, is unknown. This may be a relevant issue because chronic elevation of glucose or FFAs is known to inhibit insulin secretion in isolated pancreatic islets (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), and these abnormalities occur frequently in diabetic patients and negatively affect ␤-cell function. Moreover, experiments in isolated rat islets indicate that a glucose-FFA cycle (termed the Randle cycle [22]) with a reciprocal relationship between glucose and FFA metabolism is operative in the ␤-cell (23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, whether metformin also affects glucose and FFA oxidation in other tissues, including the pancreatic ␤-cells, is unknown. This may be a relevant issue because chronic elevation of glucose or FFAs is known to inhibit insulin secretion in isolated pancreatic islets (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), and these abnormalities occur frequently in diabetic patients and negatively affect ␤-cell function. Moreover, experiments in isolated rat islets indicate that a glucose-FFA cycle (termed the Randle cycle [22]) with a reciprocal relationship between glucose and FFA metabolism is operative in the ␤-cell (23).…”
mentioning
confidence: 99%
“…Glucose oxidation was determined by measuring the formation of 14 CO 2 from [U-14 C]glucose (27). Groups of 15 islets were incubated in a plastic cup in 100 µl of KRBB (118 mmol/l NaCl, 4.8 mmol/l KCl, 2.5 mmol/l CaCl 2 , 1.2 mmol/l MgSO 4 , 1.2 mmol/l KH 2 PO 4 , 25 mmol/l NaHCO 3 ) supplemented with 10 mmol/l HEPES (pH 7.4) containing 3 µCi D-[U- 14 C]glucose (specific activity, 302 mCi/mmol) plus nonradioactive glucose to a final concentration of either 1.5 or 16.7 mmol/l. The cups, which were suspended in standard 20-ml glass scintillation vials, were gassed with O 2 :CO 2 (95:5%) and were capped airtight.…”
mentioning
confidence: 99%
“…In these patients, the mechanisms that cause the progressive ␤-cell failure are currently under investigation: the altered insulin secretory pattern depends, at least in part, on the negative influence of chronic high glucose (5)(6)(7)(8) and/or high free fatty acid (FFA) (9 -12) plasma concentrations (gluco-or lipotoxicity). These metabolites are believed to affect pancreatic ␤-cell function by chronic ␤-cell stimulation and consequent "desensitization" to glucose.…”
mentioning
confidence: 99%
“…Although the sulphonylureas continue to be used in the treatment of type 2 diabetes mellitus, long-term clinical studies have reported a secondary failure in increasing insulin secretion (Groop 1992). The cause of this 'secondary-failure' has been the subject of several investigations and have been ascribed to ' -cell exhaustion' (Schauder et al 1977, Gullo et al 1991, Rabuazzo et al 1992) and/or ' -cell desensitization' to glucose (Hoenig et al 1986, Bolaffi et al 1988, Purrello et al 1989 or other secretagogues (Grodsky 1989). An in vitro experiment (Gullo et al 1991) has shown that 24 h exposure of islets to 100 nmol/l glibenclamide did not deplete the insulin content, suggesting that mechanisms other than insulin depletion are operative which contribute to the reduced insulin.…”
Section: Discussionmentioning
confidence: 99%